The burden of Black religion - Evans, Curtis J. (Curtis Junius); Oxford eBooks (Oxford : Oxford University Press, 2008)
In the long and tortured history of American ideas about race religion has played a prominent role. In this book, Curtis Evans traces ideas about African American religion from the antebellum period to the middle of the 20th century. Central to the story he argues, is the popular notion that blacks were somehow 'naturally' religious.
Description based on print version record.
Includes bibliographical references and index.
Keywords: African Americans -- Religion; Black theology; United States -- Church history; Electronic books